2008
DOI: 10.1103/physrevb.77.115349
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and diameter dependence of the electronic and physical properties of GaN nanowires from first principles

Abstract: We present a comprehensive first-principles investigation of the atomic and electronic structures of gallium nitride nanowires, and examine the dependence on nanowire diameter and shape. We consider nanowires in the [0001] growth direction, with diameters ranging from 8 to 35 Å, and investigate the influence of saturating the dangling bonds at the edges of nanowires. We find that unsaturated nanowires are semi-conducting and contain dangling bond states in the region of the band gap, the positions of which rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
70
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 70 publications
21
70
0
Order By: Relevance
“…We generate GaN nanodots using our previously reported wurtzite bulk GaN (a=3.18Å, c=5.18Å, u=0.377) structure. [23] Nanodots of varying sizes are generated, where we saturate the dangling bonds at the surface with appropriately chosen fractional charge hydrogen atoms (a charge of 0.75e or 1.25e, depending on whether the dangling bond is on a nitrogen or gallium atom, respectively). This ensures that effectively bulk-like GaN bonds are formed, as has been suggested for saturating dangling bonds of semiconductor compounds.…”
Section: Methodsmentioning
confidence: 99%
“…We generate GaN nanodots using our previously reported wurtzite bulk GaN (a=3.18Å, c=5.18Å, u=0.377) structure. [23] Nanodots of varying sizes are generated, where we saturate the dangling bonds at the surface with appropriately chosen fractional charge hydrogen atoms (a charge of 0.75e or 1.25e, depending on whether the dangling bond is on a nitrogen or gallium atom, respectively). This ensures that effectively bulk-like GaN bonds are formed, as has been suggested for saturating dangling bonds of semiconductor compounds.…”
Section: Methodsmentioning
confidence: 99%
“…The first principles was performed to study Hex-GaN NWs with diameters ranging 11 to 32 Å, found that n is 1.17. 30 Carter et al 14 reported the value of n for hexagonal wires form SIESTA is 1.17 and from DMOL 3 is 1.46. But the Tri-angular wires have a small value of n is 0.901 and 0.965 form SIESTA and DMOL.…”
Section: A Geometry Effect On Bandgap Of Gan Nanowiresmentioning
confidence: 99%
“…3 shows, which is agreeable with previous study. 14 We further investigate the dependence of bandgap on transverse size with different cross sections. Fig.…”
Section: A Geometry Effect On Bandgap Of Gan Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)], z 0 = 100 nm is the position of its center (measured with respect to the source, for which z = 0), the nanowire has length L = 200 nm, r 0 = 20 nm is the radius of the nanowire outside the constriction region, and r c is the radius of the nanowire in the middle of the constriction. Since for the values of r c less then ∼5 nm the band structure strongly depends on the geometric parameters of the nanosystems, 36,37 and thus the effective mass approximation is no longer valid, we limit our calculations to r c > 10 nm.…”
mentioning
confidence: 99%